Vacuum effect on DNA lesion and genetic mutation of cells - S. Sarapirom (2018)
DNA topological forms can be changed by environmental factors thus to potentially cause genetic mutation. Vacuum of low pressure is considered to be such a factor. An investigation was carried out to check topological form changes of extracellular plasmid DNA due to lesion in DNA under the vacuum condition. Pumping the experimental stage of biological samples to vacuum may result in three effects on the environment of the sample, namely, low pressure, low temperature and low humidity, all of which may impact DNA. In the experiment, the DNA topological form change and related lesion after plasmid DNA samples were exposed to vacuum with varied time was analyzed with gel electrophoresis and fluorometric assay. The electrophoresis results were quantified to obtain percentages of the supercoiled and relaxed forms but no linear form of DNA. The fluorometer measured concentrations of single strand and double strand DNAs. The results showed that the single strand break was the dominant lesion in DNA. The DNA form change and the lesion were found to depend mainly on the pressure change but not much on the pressure itself. The vacuum-exposed DNA was subsequently transformed into bacteria Escherichia coli (E. coli) for checking mutation occurrence. No observable mutation of the DNA-transformed bacteria was found. This study concluded that certain light lesion in DNA dominated by the single strand break could be induced by vacuum exposure but with negligible risk of genetic mutation. Crown Copyright © 2011 Published by Elsevier Ltd. All rights reserved.